(untitled) (Research, Society and Development, 2022)
Market research makes it possible to obtain important information and data for management and development in the industry. In this view, the main objective of this research was to obtain the profile of consumers and non-consumers of vanilla. This is because vanilla is one of the most important spices for the food industry, and in Brazil, despite having species of market potential, the import and use of artificial vanilla is what predominates. Therefore, an online questionnaire was applied to obtain information about the vanilla scenario in Brazil. The results showed that the most respondents are consumers of vanilla essence, and most of them do not know vanilla in its natural form, and also do not have the habit of consuming it, with the main justifications being the lack of availability and the price. Natural vanilla consumers earn the highest income and live in regions where vanilla species occur, which facilitates access. A big number of people consume products that contain vanilla, evidencing the importance of the spice for the industry. Regarding Brazilian vanilla species, most did not know or said they did not exist. The results of this research make evident the importance of disseminating information about native vanilla species and their potential, since most respondents were willing to buy Brazilian vanilla. Therefore, encouraging research and production is of paramount importance for the recognition of Brazilian vanilla species.